USDA Organic Certification: Who Should Be Certified? - James J. Ferguson (EDIS)
According to The National Organic Program (NOP) any “farm, wild crop harvesting, or handling operation (processors and manufacturers) that wants to sell an agricultural product as organically produced must adhere to the national organic standards.” This means that USDA certified organic farmers and handlers must have an organic system plan approved by an accredited certifying agent and use materials in accordance with the National List of Allowed Synthetic and Prohibited Nonsynthetic substances. This document is HS970, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: March 2004.